Health and medical experience of migrant workers: qualitative meta-synthesis - Hyun-Jin Cho; Kyoungrim Kang; Kyo-Yeon Park (BMC, 2024)
Abstract Background Migrant workers in Korea are contributing to economic development by resolving labour shortages due to the increase in the ageing population, and they have become necessary and important in the Korean economy. However, long working hours, poor working conditions, and cultural differences can cause migrant workers to experience disadvantages in using health and medical services. Therefore, this study aimed to understand and analyse the health and medical service experience of migrant workers in Korea by reviewing previous studies in order to improve their health and access to medical services. Method The qualitative meta-synthesis method suggested by Thomas and Harden was used. The key question for searching the literature is 'What is the status of the use of health and medical service by migrant workers in Korea and the attributes that affect them?' Five electronic databases (RISS, KCI, KISS, Science ON, and KMbase) were searched for Korean literature published in academic journals until 6 November 2022 using a combination of "migrant worker or foreign worker or foreign labourer or migrant" and "medical or health" in Korean. Results A total of nine studies out of 1,006 were included in the review after methodological quality assessment using the Critical Appraisal Skills Program (CASP). The results of studies were synthesised into three themes and ten sub-themes: 'Personal factors' of personal health beliefs and the financial burden of healthcare costs; 'Cultural factors' of cultural differences in the lifestyle, cultural differences in the healthcare environment, and traditional medicine in the country; and 'Socio-institutional factors' of poor and difficult working environment, insufficient information about medical institutions, policies with a lack of practical applicability, systems of healthcare institutions, and healthcare services usage. Conclusions This study identified the experiences of migrant workers in using health and medical care services. The results of this study can be used as a basis for improving the health of migrant workers and access to healthcare services. Based on the results of this study, it is necessary to improve the health management ability of migrant workers by developing a health management platform that can support Korean medical information and provide professional and accurate self-health management information.